1994
DOI: 10.1080/01652176.1994.9694410
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of serum Amyloid‐a (SAA) and haptoglobin (HP) as parameters of inflammatory diseases in cattle

Abstract: SUMMARYThe concentrations of the acute-phase proteins, serum amyloid-A (SAA) and haptoglobin (Hp), were determined in the plasma of healthy cows (n=25) and cows with spontaneous acute (n=6), subacute (n=37), or chronic (n=7) inflammatory diseases. The plasma concentration of SAA alone, Hp alone, and the Hp/SAA ratio, differed significantly (p<0.001) between healthy animals and animals with inflammatory diseases. Plasma Hp concentrations in the group of cows with acute inflammatory diseases were significantly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
150
2
6

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(176 citation statements)
references
References 20 publications
12
150
2
6
Order By: Relevance
“…Hp is the most sensitive marker of inflammation in cows [2,7,8]. Since most of the cows suffering from amyloidosis examined in the present study showed increases in both SAA and Hp levels, it was thought that the increase in SAA level was mainly caused by concomitant inflammation.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Hp is the most sensitive marker of inflammation in cows [2,7,8]. Since most of the cows suffering from amyloidosis examined in the present study showed increases in both SAA and Hp levels, it was thought that the increase in SAA level was mainly caused by concomitant inflammation.…”
mentioning
confidence: 88%
“…SAA levels in cows with various diseases have been reported only recently [2,3,5,8,9], but the levels are not routinely measured yet, and there has been only one publication on the determination of the serum SAA level in a cow with amyloidosis [1].…”
mentioning
confidence: 99%
“…Serum amyloid A (SAA) is a sensitive APP in cattle [1,8,11,13,24]. SAA has been shown to reflect the severity of mastitis; cows with clinical mastitis had almost 100-fold levels of SAA in serum and milk compared with healthy cows [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies noted that the concentrations of SAA and haptoglobin remained at normal ranges during experimentally created bacterial and aseptic infections (ALSEMGEEST et al, 1994;NAKAGAWA et al, 1997).…”
Section: Discussionmentioning
confidence: 99%